Avaliação de programas nutricionais com a utilização de enzimas em rações de frangos de corte - FORTES, Bruno Duarte Alves (2010)
The experiment was conducted to evaluate different programs Nutritional supplementation of carbohydrases and phytase enzymes) in broiler diets on performance and carcass yield. We used the test in 2016 male chicks a day, Cobb-500 distributed in 32 boxes of 2.10 m x 2.50 m. We used a randomized complete block design with two blocks (sheds), four treatments, four replicates and 63 birds per plot. The experimental diets were based on corn and soybean meal. The treatments were: T1) Nutritional program Cobb, T2) 4% reduction in metabolizable energy (ME), 3% crude protein (CP) and 10% of the recommendations of the amino acids of T1, T3) reformulated Diet isonutriente to T1 with 200 g / t carbohydrases ( beta-glucanase, xylanase, alpha-galactosidase and Galactomannanase) + 50 g / t phytase, T4) reformulated Diet isonutriente to T2 with 200 g / t carbohydrases (beta-glucanase, xylanase, alpha-galactosidase and Galactomannanase) + 50 g / t phytase. There were no differences on the feed phase integral (1-42dias) created for the different treatments. However, feed intake and weight gain were affected (P <0.05), where the treatments supplemented with enzymes had higher feed intake than the treatments without enzyme supplementation is consistent with the weight gain in the treatments 3 and 4 showed weight gains higher than treatments 1 and 2. It is concluded that the use of carbohydrases associated with inclusion of phytase was effective to elevate the metabolizable energy of diets based on corn and soybean meal, and that the addition of enzymes in the diet of the birds led to an increase in food consumption of 5 , 18%, and improved weight gain of 4.39% and did not affect carcass characteristics